2012
DOI: 10.1002/stem.1251
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF‐β/Smad Signaling by BAMBI Blocks Differentiation of Human Mesenchymal Stem Cells to Carcinoma‐Associated Fibroblasts and Abolishes their Protumor Effects

Abstract: Bone marrow mesenchymal stem cells (BM-MSCs) have multiple therapeutic potentials for regenerative, antiinflammatory, and immunomodulatory purposes and also show promise as vehicles for gene therapy of various metastatic cancers based on their tumor-tropic capacity. However, BM-MSCs are also a source of carcinoma-associated fibroblasts (CAFs) and may promote growth and metastasis of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 45 publications
1
99
0
Order By: Relevance
“…In vivo experiment showed that BAMBI transduction abolished protumor effects of an orthotopic breast cancer xenograft model (43) and modulated the effects of diabetes via inhibiting TGF-β signaling (44). Our study found that BAMBI overex pression and β-sitosterol suppressed tumor growth in NSCLC xenografts, revealing the antitumor effect of BAMBI overexpression and β-sitosterol.…”
Section: Discussionmentioning
confidence: 54%
“…In vivo experiment showed that BAMBI transduction abolished protumor effects of an orthotopic breast cancer xenograft model (43) and modulated the effects of diabetes via inhibiting TGF-β signaling (44). Our study found that BAMBI overex pression and β-sitosterol suppressed tumor growth in NSCLC xenografts, revealing the antitumor effect of BAMBI overexpression and β-sitosterol.…”
Section: Discussionmentioning
confidence: 54%
“…Published reports indicate that prolonged stimulation of BM-derived human MSCs with breast tumor-derived factors (Tumor CM) has led to conversion of MSCs into functional CAFs that promoted tumor growth [11-14]. We began this study by determining the influence of such tumor-derived factors on the inflammatory traits of CAFs generated by MSCs exposed to Tumor CM, using the expression of the inflammatory/pro-malignancy chemokines CCL2, CXCL8 and CCL5 as readouts.…”
Section: Resultsmentioning
confidence: 99%
“…Such MSCs, originating in bone marrow (BM) or adipose tissues generally have pro-cancerous effects that promote malignancy in many tumor systems, including breast cancer [5-12]. In vitro , tumor cell products that are present in tumor-derived conditioned medium (CM) convert MSCs to CAFs which become fully and potently functional in promoting malignancy in vivo [11-14]. …”
Section: Introductionmentioning
confidence: 99%
“…For cancer cells producing a high level of IL1 such as in LoVo colon cancer cells and HCC1806 breast cancer cells, BM-MSCs are activated by tumor-derived IL1 to produce protumor factors such as PGE2 and IL6 to promote cancer progression (19). For cancer cells producing a low level of IL1, such as MDA-MB-231 (widely metastatic) and MCF7 (noninvasive) breast cancer cells, (i) hyaluronan produced by MSCs activates the CD44 pathway in cancers to induce LOX expression and promote the EMT and invasion of cancer cells (42); and (ii) TGFβ produced by cancer cells or tumor stromal cells promotes expression of protumor factors such as IL6 and SDF1 by BM-MSCs (4,38). Intriguingly, the expression of multiple genes related to these three pathways, including receptors for IL1 and TGFβ, IL6, SDF1, and the synthases of PGE2 and hyaluronan, as well as the production of PGE2 and hyaluronan, was dramatically lower in iPSC-MSCs with or without exposure to tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%